2013
DOI: 10.1016/j.molonc.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐targeting TRAIL expression mediated by miRNA response elements suppressed growth of uveal melanoma cells

Abstract: Adenovirus miRNA TRAIL A B S T R A C TMalignant uveal melanoma severely damages eye function and is prone to metastasize to other organs. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising agent to treat uveal melanoma because of its induction of apoptosis in cancer cells both at primary and metastatic sites. However, TRAIL therapy lacks tumor specificity in the current delivery systems for uveal melanoma treatment, thereby causing cytotoxiciy to normal tissues. To improve uveal mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
2
30
0
1
Order By: Relevance
“…Finally, in vivo data revealed that Ad-TRAIL-MRE-7-122 suppressed the growth of Bcap37 tumors in mice as potent as Ad-TRAIL and had no hepatotoxicity to the animals. In fact, the similar effects have been verified in some other types of cancers using MRE-based strategy, such as melanoma, glioma and bladder carcinoma [11][12][13].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Finally, in vivo data revealed that Ad-TRAIL-MRE-7-122 suppressed the growth of Bcap37 tumors in mice as potent as Ad-TRAIL and had no hepatotoxicity to the animals. In fact, the similar effects have been verified in some other types of cancers using MRE-based strategy, such as melanoma, glioma and bladder carcinoma [11][12][13].…”
Section: Discussionsupporting
confidence: 60%
“…More importantly, the expression of inserted genes can be suppressed in normal cells because of the overexpression of selected miRNAs. However, no publication that focuses on the MRE-regulated gene therapy for breast cancer is available, although this strategy has been tested for some other types of cancer [11][12][13][14].…”
mentioning
confidence: 99%
“…Northern blot analysis was performed to determine the levels of miR-155 in the indicated samples and cell lines, according to previously described procedures (13). Briefly, total RNA was isolated from the tissues and cells using TRIzol reagent (Invitrogen Life Technologies, Carlsbad, CA, USA), which was then separated using 15% urea-PAGE (8 M; 480 g urea/liter; Sigma-Aldrich).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Northern blot analysis was performed according to the procedures previously described [9]. miR-155 inhibitor and mimics mirVana™ miRNA inhibitors and mimics specific for miR-155 (Invitrogen, USA) were used to increase and silence the expression of miR-155, respectively, in glioma cell lines and primary astrocytes.…”
Section: Quantitative Pcrmentioning
confidence: 99%